EFEKTIVITAS MODEL INKUIRI SOSIAL TERHADAP KETERAMPILAN SOSIAL DAN PARTISIPASI SISWA KELAS TINGGI SD - Neza (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This study aims to analyze the effectiveness of the social inquiry learning model on the social skills and participation of upper-grade elementary school students. The social inquiry model emphasizes the investigation of social issues through discussion, group work, and reflection, encouraging students to actively interact and think critically. This research employed a quantitative approach with a quasi-experimental design. The participants were upper-grade elementary school students divided into an experimental class and a control class. Data were collected through observation, social skills questionnaires, and student participation assessment sheets. The findings indicate that the implementation of the social inquiry model significantly improves students’ social skills and participation compared to conventional teaching methods. Students became more active in discussions, demonstrated better cooperation, and showed mutual respect during the learning process. Therefore, the social inquiry model can serve as an effective alternative approach to enhance social skills and increase student participation in upper-grade elementary classrooms.